Recent Developments of Microenvironment Engineering of Single‐Atom Catalysts for Oxygen Reduction toward Desired Activity and Selectivity - Li, Longbin; Huang, Bingyu; Tang, Xiannong; Hong, Yaoshuai; Zhai, Weijuan; Hu, Ting; Yuan, Kai; Chen, Yiwang (Advanced functional materials, 2021)
Oxygen reduction reaction (ORR) is an essential process for sustainable energy supply and sufficient chemical production in modern society. Single‐atom catalysts (SACs) exhibit great potential on maximum atomic efficiency, high ORR activity, and stability, making them attractive candidates for pursuing next‐generation catalysts. Despite substantial efforts being made on building diversiform single‐atom active sites (SAASs), the performance of the obtained catalysts is still unsatisfactory. Fortunately, microenvironment regulation of SACs provides opportunities to improve activity and selectivity for ORR. In this review, first, ORR mechanism pathways on N‐coordinated SAAS, electrochemical evaluation, and characterization of SAAS are displayed. In addition, recent developments in tuning microenvironment of SACs are systematically summarized, especially, strategies for microenvironment modulation are introduced in detail for boosting the intrinsic 4e−/2e− ORR activity and selectivity. Theoretical calculations and cutting‐edge characterization techniques are united and discussed for fundamental understanding of the synthesis–construction–performance correlations. Furthermore, the techniques for building SAAS and tuning their microenvironment are comprehensively overviewed to acquire outstanding SACs. Lastly, by proposing perspectives for the remaining challenges of SACs and infant microenvironment engineering, the future directions of ORR SACs and other analogous procedures are pointed out. The microenvironment of single‐atom catalysts (SACs) is important to determine their catalytic performance. This review mainly summarizes the recent progress in microenvironment engineering of SACs toward desired activity and 4e−/2e− selectivity for oxygen reduction reaction. Moreover, the remaining challenges and prospects for microenvironment engineering of SACs are also presented.